2016
DOI: 10.18632/oncotarget.9544
|View full text |Cite
|
Sign up to set email alerts
|

FAM83 proteins: Fostering new interactions to drive oncogenic signaling and therapeutic resistance

Abstract: The FAM83 proteins were recently identified as novel transforming oncogenes that function as intermediaries in EGFR/RAS signaling. Using two distinct forward genetics screens, the Bissell and Jackson laboratories uncovered the importance of the FAM83 proteins in promoting resistance to EGFR tyrosine kinase inhibitors and therapies targeting downstream EGFR signaling effectors. The discovery of this novel oncogene family using distinct genetic screens provides compelling evidence that the FAM83 proteins are key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 111 publications
1
41
0
Order By: Relevance
“…Interestingly, in breast cancer, FAM83B is expressed at higher levels in tumors without estrogen and progesterone receptors or human EGFR-2, compared with receptor-positive tumors ( 21 ). Furthermore, FAM83H , the paralog of FAM83B , is overexpressed in androgen independent-prostate cancer ( 22 ). These findings could indicate that FAM83B has an oncogenic role without aberrant signals from driver gene mutations or overexpressed hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in breast cancer, FAM83B is expressed at higher levels in tumors without estrogen and progesterone receptors or human EGFR-2, compared with receptor-positive tumors ( 21 ). Furthermore, FAM83H , the paralog of FAM83B , is overexpressed in androgen independent-prostate cancer ( 22 ). These findings could indicate that FAM83B has an oncogenic role without aberrant signals from driver gene mutations or overexpressed hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Our knockdown study of FAM83B showed that its expression was associated with tumor proliferation in cell lines expressing high levels of FAM83B ; however, H1975 cells showed that knockdown of low levels of FAM83B also inhibited proliferation. Of all the FAM83 members, only FAM83H knockout mice, which live for only 2 weeks, have been reported, and FAM83H is proposed to play a role in the maintenance of cell homeostasis ( 22 , 28 ). Other FAM83 family members, including FAM83B , may also be required at certain levels, even in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Family with sequence similarity 83 (FAM83) oncogenes were discovered by two screens separately [6,7]. Recently, multiple studies have identified overexpressed or dysregulated FAM83 members in cancer [8]. Among the eight FAM83 family genes (FAM83A-H), the 434-amino acid FAM83A protein is the smallest one.…”
Section: Introductionmentioning
confidence: 99%
“…They have oncogenic potential and are frequently upregulated in human tumours. 7,8 Fam83F has 500 amino acids and a molecular weight of 55 kDa. It is highly expressed in platelets, pancreas, the gastrointestinal tract and testis.…”
Section: Introductionmentioning
confidence: 99%